Developing a current capability design for manufacture framework in the aerospace industry - Whiteside, A.; Shehab, Essam; Beadle, Chris; Percival, M. (Cranfield University Press, 2009)
During progressive product design and development in the aerospace industry, a lack of effective communication between the sequential functions of design, manufacturing and assembly often causes delays and setbacks whereby production capabilities are unable to realise design intent in high-complexity product models. As a result, there is a need to formalise the progressive release of an engineering model to production functions during New Product Introduction (NPI) via defining key stages of definition maturity and information requirements through a structured process. This paper describes the development of a framework to facilitate optimal ‘design for manufacture’ based on current manufacturing capabilities within the aerospace industry.
Organised by: Cranfield University
Keywords: Design for Manufacture and Assembly; Process Capability Analysis; Aerospace Industry